factoring is one of those things that is really terrible, aks your teacher for help right away, dont feel bad though, every year I've had math(and I took university level courses) we had to relearn factoring because it is a pile of suck. I've tried having some one teach me it online and it just wont stick, get some help from ur teach, 1 on 1 stuffs.
2006-09-12 17:52:09
·
answer #1
·
answered by kingoftheintertron 3
·
0⤊
0⤋
Factoring 60x-42
1. consider the two numbers 60 and 42. what are the common prime factors?
60 = 2 X 2 X 3 X 5
42 = 2 X 3 X 7
the common factors are 2X3 = 6
therefore 60 = 6 X 10 and 42 = 6 X 7
rewrite the formula as (6*10)x - (6*7)
the common factor of 6 can be rewritten as 6*(10x-7)
2006-09-12 17:51:48
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
Ok, well i'll try to explain! to put something in factored form means to find what these numbers have in common. For instance:
ex:2
4x^2 - 196 ---> are both divided by four, so:
4 (x^2 - 64) -----> 64 is 8^2 and u write it like
4 (x^2 - 8^2) -----> the formula for (x^2- y^2)=(x+y)(x-y) so we further it down to:
4(x+8)(x-8)
Ex:3
9x^2 - 1 = 3^2 x^2 - 1= (3x)^2 - 1^2 = (3x-1)(3x+1)
The first example, hmm, try it urself... it helps more!
2006-09-12 17:49:58
·
answer #3
·
answered by becko 1
·
1⤊
0⤋
This is all about factoring. In the first problem, you can factor out a 6 from each term to get 6*(10x - 7)
In the 2'nd one, you can factor out a 4 from each term to get 4*(x² - 49) and you can then factor (x² - 49) into
(x+7)*(x-7) so that the full factored result is 4*(x+7)*(x-7)
In the 3'rd one 9x² is a perfect square (3x)² fo it factors into (3x+1)*(3x-1)
OK?
Doug
2006-09-12 17:41:35
·
answer #4
·
answered by doug_donaghue 7
·
1⤊
1⤋
60x - 42 = 6(10x - 7)
4x^2 - 196 = 4(x^2 - 49) = 4(x - 7)(x + 7)
9x^2 - 1 = (3x - 1)(3x + 1)
2006-09-12 18:31:38
·
answer #5
·
answered by Sherman81 6
·
1⤊
0⤋
60x-42=3(20x-14)=6(10x-7)
4x^2-196=(2x+14)(2x-14)
9x^2-1=(3x+1)(3x-1)
Explanation for 9x^2-1=(3x+1)(3x-1):
You have to figure out what foiled will produce
9x^2-1.
3x * 3x = 9x^2, good to go.
-3x + 3x = 0, good to go.
1 * -1 = -1, that's it, as long as your teacher taught you how to foil and unfoil. ...
I will not trust our educational system.
When dealing with a binomial that is a difference(-) of squares(x^2, 4, 9, ... n^2),
it will be equivalent to a binomial times a binomial of the form:
(x+c)(x-c)=(x^2-c^2).
Enjoy;)
2006-09-12 18:26:39
·
answer #6
·
answered by numberone 1
·
0⤊
0⤋
60x-42=6(10x - 7)
4x^2-196=4(x^2-49)=4(x-7)(x+7)
9x^2-1=(3x-1)(3x+1)
2006-09-12 17:43:01
·
answer #7
·
answered by Anonymous
·
1⤊
0⤋
it is actually not hard. break up into parts.. u see
60x-42= 6(10x-7) (Factorise by 6)
4x^2-196= 2^2x^2- 13^2 (Using formular a^2 - b^2)
=(2x)^2 - (13)^2
=(2x +13) (2x-13)
9x^2-1 (This is the same as the previous question)
= 3^2x^2-1^2
=(3x)^2- (1)^2
= (3x+1) (3x-1)
YUP!
2006-09-12 17:43:59
·
answer #8
·
answered by Anonymous
·
1⤊
1⤋
in case you stated NO, and he persevered and compelled himself into you, it really is RAPE! do not be at a loss for words that you've been raped by employing your cherished, you've been raped by employing someone that manipulated you to be in love with him; a monster donning an innocuous mask and outfits. do not placed off reporting this to the police because you've been tricked into believing you've been in love with one yet another and abstaining from sexual kin
2016-11-26 20:45:34
·
answer #9
·
answered by ? 4
·
0⤊
0⤋
If you don't understand it you need to ask your teacher to help you better understand it before he/she moves on to something else or the same thing just another level.
2006-09-12 17:43:54
·
answer #10
·
answered by Anonymous
·
1⤊
0⤋